Pengaruh Penggunaan Media Sosial terhadap Pembelian Impulsif Produk Skincare Viral dengan FOMO sebagai Variabel Mediasi pada Generasi Z di Kota Makassar - Siska Handayani; Burhanuddin Burhanuddin; Ilma Wulansari Hasdiansa; Sitti Hasbiah; Isma Azis Riu (Yayasan Literasi Sains Indonesia, 2026)
This study aims to analyze the influence of social media usage on impulse purchases of viral skincare products and to examine the role of Fear of Missing Out (FOMO) as a mediating variable among Generation Z in Makassar City. Specifically, this research investigates: (1) the effect of social media usage on impulse purchases, (2) the effect of social media usage on FOMO, (3) the effect of FOMO on impulse purchases, and (4) the mediating role of FOMO in the relationship between social media usage and impulse purchases. This study employs a quantitative approach with an explanatory research design to explain causal relationships among the variables. Data were collected through questionnaires distributed to 180 Generation Z respondents in Makassar City who had purchased or were familiar with viral skincare products promoted through social media platforms. The data analysis technique used was Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4.0 software. The analysis included outer model testing to evaluate validity and reliability, as well as inner model testing to assess direct and indirect relationships using the bootstrapping method. The results show that all proposed hypotheses are supported. Social media usage has a positive and significant effect on impulse purchases and significantly increases FOMO. Furthermore, FOMO positively and significantly influences impulse purchases and partially mediates the relationship between social media usage and impulse purchases. These findings highlight the important role of emotional and psychological factors in shaping impulsive buying behavior among Generation Z.